Overweight and Obese Children's Ability to Report Energy Intake Using Digital Camera Food Records during a 2-Year Study. (16th August 2012) - Svensson, Åsa; Waling, Maria; Bäcklund, Catharina; Larsson, Christel
Abstract : The objective was to evaluate overweight and obese children's ability to report reproducible and valid estimates of energy intake (EI) by using digital camera food records (FR) during a 2-year study, compared with objectively measured total energy expenditure (TEE). Seventy-three overweight/obese children, aged 8–12 years at inclusion, kept FR with the help of digital cameras for 16 days in total, on 7 occasions during a 2-year period. On the same days, their TEE was registered with SenseWear Armband (SWA). The children underestimated their EI by −2.8 (2.4) MJ/d on the first assessment occasion (95% CI: −3.3, −2.3). Reporting accuracy did not differ between the 7 assessment occasions (P = 0.15 ). Variables negatively associated with reporting accuracy relative to TEE were increased age (95% CI: −0.07, −0.01) and BMI z-score (95% CI: −0.18, −0.06). Further, reporting accuracy relative to TEE was lower for girls than boys (95% CI: −0.14, −0.01) and on weekdays compared with weekend days (95% CI: −0.08, −0.001). In conclusion, overweight and obese children were able to report their EI using a digital camera FR with good reproducibility over a 2-year period, even though their EI was underestimated compared with objectively measured TEE.